The Relationship Of Compensation And Motivation To Employee Performance At PT. KB Finansia Multi Finance Bandengan Jakarta Utara Branch - mario, Mario Rivaldo; Suzanna Josephine LTobing; L.Toruan, Rutman (Universitas Kristen Indonesia, 2024)
In this age of globalization, trustworthy human resources are essential. In order to accomplish their objectives, businesses constantly look for resources that can work efficiently and effectively. Human resources that are both competent and perform well can be a boon to a company's bottom line, while those that are neither can lead to financial disaster. An approach based on quantitative methods is employed. The foundation of this rests on statistical studies and data collected from a specific demographic. Asking people specific questions is the backbone of the quantitative approach, which aims to verify hypotheses through data collection. With 42 participants, 42 degrees of autonomy, and a t-table and a signifance level 0f 0.005, the results for the two-way test are 2.018. Following from the previous summary, We can a meaningful association between compensation employee performance because the t-count (5.431) is larger than the t-table (2.018) and the sig value (0.000) is less than 0.05. Therefore, we reject Ho and accept Ha. With a total sample size of 42, a degree of autonomy (db) of 42 for two-way weighing, and a significance level of 0.05, we get the following t-table: 2.018. According to the summary, the t-count (4.688) is higher the t-table (2.018), and the sig value (0.001) is less than 0.05. Therefore, can reject Ho and accept Ha, indicating a significant relationship between employee motivation and job performance. Compensation should be based on what employees deserve if the company wants to see improved performance from its employees. Giving out awards to deserving employees is another way for the company to boost performance; it makes them feel appreciated, which in turn motivates them to work harder. Keywords: Compensation, Motivation, Employee Performance